Definition of halal analysis of formulation of kombucha drink from simplicia of malay apple fruit (Syzygium malaccense) - Lubis, Novriyanti; Mubarok, Anwar; Junaedi, Effan Cahyati; Soni, Dang (Journal of Halal Product and Research (JHPR), 2024)
The wealth of biodiversity and the abundance of native Indonesian germplasm resources have not been optimally utilized domestically. Malay apple, which belongs to the myrtaceae family, has various health benefits. However, its utilization is still limited, thus requiring ideas to increase public interest in this fruit. Therefore, innovation is carried out by transforming malay apple  into kombucha fermentation beverages as a step to optimize its utilization. The research aimed to measure the total alcohol content, total acid, and total sugar in the formulation of kombucha beverages derived from malay apple  fruit juice, with the goal of developing it into a functional beverage. The research process involved testing alcohol content using gas chromatography, measuring total acid by alkalimetric titration method, and measuring total sugar content by anthrone method. The research results showed that the malay apple  kombucha sample  the level  of alcohol content was 0.0213%, the total acid was 1.38% (<2 g/L), and the total sugar was 0.807 µg. The kombucha malay apple which category halal kombucha.